2001
DOI: 10.1002/1096-9896(2000)9999:9999<::aid-path719>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 immunoquantitation in cervical intraepithelial neoplasia (CIN): a sensitive marker for grading

Abstract: The aim of this study was to assess the value of Ki-67 immunoquantitation with a computerized image analysis system for grading support in cervical intraepithelial neoplasia (CIN). Sixty-five 'blind' consensus biopsies (23 CIN 1, 22 CIN 2, and 20 CIN 3) were used as a learning set. Measurements were done in the carefully selected most severely dysplastic part of the epithelium of each CIN case. The resulting discriminating combination of quantitative features was then prospectively applied on 121 new biopsies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
8

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 12 publications
2
30
0
8
Order By: Relevance
“…A significant gradual increase of the total number of Ki-67Ypositive nuclei in accordance with the severity of the dysplasia, showing an increase in the cell proliferation rate, has also been previously demonstrated. 9,15 These results suggest excellent reproducibility of the Ki-67 immunohistochemistry, which offers the possibility of its use for diagnostic purposes. Although Kruse et al revealed even better results using a computerized image analysis system and calculating the stratification index (the ratio between the distance from the nucleus to the basal membrane and the thickness of the epithelium), we think that a simple analysis system, which correctly divides the epithelium into three thirds, is sufficient to assess the pattern of Ki-67 positivity within the epithelium.…”
Section: Discussionmentioning
confidence: 60%
“…A significant gradual increase of the total number of Ki-67Ypositive nuclei in accordance with the severity of the dysplasia, showing an increase in the cell proliferation rate, has also been previously demonstrated. 9,15 These results suggest excellent reproducibility of the Ki-67 immunohistochemistry, which offers the possibility of its use for diagnostic purposes. Although Kruse et al revealed even better results using a computerized image analysis system and calculating the stratification index (the ratio between the distance from the nucleus to the basal membrane and the thickness of the epithelium), we think that a simple analysis system, which correctly divides the epithelium into three thirds, is sufficient to assess the pattern of Ki-67 positivity within the epithelium.…”
Section: Discussionmentioning
confidence: 60%
“…Immunoquantitation of Ki-67 is an important diagnostic adjunct for grading of CIN [53][54][55] and also in distinguishing CIN from normal or benign reactive cervical squamoepithelial lesions. The combination of the Stratification Index (SI, which indicates, how high Ki-67-positive nuclei are located in the epithelium; the higher the SI, the higher the CIN grade) and the number of Ki-67 positive nuclei located in the middle third layer of the epithelium per 100 lm basal membrane (the more Ki-67-positive nuclei, the higher the grade) is the best discriminating set of features that distinguishes the three CIN grades at the same time.…”
Section: Ki-67mentioning
confidence: 99%
“…Immunoquantitative parameters for Ki-67 are also correlated with the presence of hrHPV in CIN lesions (fig 8). 20 …”
Section: Ki-67 and Cin Gradementioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20] Without doubt, p16 and Ki-67 are the most widely available, robust, stable and strong predictive biomarkers currently available for handling CIN lesions. (The antibody MIB-1 is often used in paraffin wax sections to assess Ki-67 expression.…”
mentioning
confidence: 99%